2016
DOI: 10.4103/0019-5545.196706
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stigma of mental illness: A comparison between two metropolitan cities in India

Abstract: Purpose:An increasing number of comparative studies are conducted on the stigmatization of persons with mental illness, in particular with regard to regional and diachronic variation. So far, there have been no studies comparing stigmatization of persons with mental illness in two different regions of India. Therefore, we examined the differences in perception of stigma attached to mental illnesses in Kolkata and Chennai, with regard to cultural and geographical differences to better understand the roots and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…And the qualitative findings showed that there were four major barriers among patients to seek care from mental health care facilities: the rejection of mental illness by patients due to fear of societal stigma, faith on magico-religious healers, lack of availability of mental health services, and poor socioeconomic conditions. A study conducted in India also revealed that factors such as lower education and females are having more of negative attitudes towards mental health care facilities [17,22]. The present study suggested that females are best weakly related to the attitudes; they are slightly more rigid with their views and have more negative attitudes.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…And the qualitative findings showed that there were four major barriers among patients to seek care from mental health care facilities: the rejection of mental illness by patients due to fear of societal stigma, faith on magico-religious healers, lack of availability of mental health services, and poor socioeconomic conditions. A study conducted in India also revealed that factors such as lower education and females are having more of negative attitudes towards mental health care facilities [17,22]. The present study suggested that females are best weakly related to the attitudes; they are slightly more rigid with their views and have more negative attitudes.…”
Section: Discussionsupporting
confidence: 48%
“…While examining the issues related to the mental health system, it was always found that level of education is the key factor responsible for the attitudes [1]. Low education levels are responsible for gaps in mental health literacy and inadequate knowledge about seeking correct treatment, which could involve not approaching the appropriate mental health care facilities needed [22]. India, with its diverse cultural and ethical systems mixed in recent years with Western approaches of thinking, makes it tough to identify a uniform and exclusive Indian paradigm of mind and mental health [7].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 22 ] However, stigma toward individuals who have mental illness in Asian countries is often disproportionally higher than that in Western countries. [ 20 48 ] In South and Southeast Asian nations, especially in India, prejudice of mentally ill people being dangerous and aggressive[ 20 23 ] adjunct with factors such as religion and lower education[ 24 ] result in a higher public desire for social distance to affected individuals. In addition to that, the substantial lack of adequate health-care providers coupled with a personal burden and the lack of awareness within the population ultimately leads to a deficient quality of mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…Our impression was that during the interview if any issues arose due to some participants being unfamiliar with the context of mental illness, it was helpful that we allowed them to take their time and instructed them that they had the chance to respond to that question later. This procedure may not necessarily be a weakness of the questionnaire and facilitated a higher completion rate.We agree et al .,[12] that in our study we did not fully follow the outlined WHO translation method, especially in terms of cognitive testing. We, thus, acknowledge the suggestion for future studies, given sufficient funding, and accept a potential inadequacy of equivalence as a limitation of our study.…”
mentioning
confidence: 52%